Does virtual reality increase emotional engagement during exposure for PTSD? Subjective distress during prolonged and virtual reality exposure therapy. (January 2019) - Reger, Greg M.; Smolenski, Derek; Norr, Aaron; Katz, Andrea; Buck, Benjamin; Rothbaum, Barbara O.
Highlights: No group differences in average or peak subjective distress during exposure therapy. Positive association between distress during first exposure and baseline PTSD symptoms. Decreased distress across treatment was associated with decreased symptoms. No group differences in the trajectory of habituation. Abstract: Prolonged exposure (PE) is a treatment for posttraumatic stress disorder (PTSD) based on emotional processing theory. According to this theory, emotional engagement during imaginal exposure is critical to clinical outcome. One rationale for virtual reality exposure therapy (VRE) is the ability of trauma-relevant, multi-sensory stimuli to increase emotional engagement. This study compared the subjective distress of active duty soldiers ( N = 108) during exposure via PE or VRE. Soldiers with higher mean or peak distress during the first imaginal exposure had higher baseline PTSD symptom severity. There was no difference between groups on average or peak distress during imaginal exposure at the first or final exposure session. There were no significant differences in between-session habituation observed between VRE and PE groups. However, each ten-point decrease in SUDS scores, either mean or peak, from the initiation of imaginal exposure to the end of treatment, was associated with a greater decrease in CAPS-W scores for both groups. There were no group differences in these trajectories or the magnitude of the association between distress/habituation, and PTSD symptoms. Future research on VRE should measure patient ratings of engagement during exposure to better understand which patients are aided by this innovative approach to treatment.